FEATURES OF CHANGES IN IMMUNOLOGICAL PARAMETERS AND DNA METHYLATION IN CHILDREN AGED 7-10 YEARS ENGAGED IN SWIMMING - Babich, Svyatoslav; Aleynik, Vladimir (Medical science of Uzbekistan, 2025)
The article deals with the features of adaptive processes for changing immunological parameters and epigenetic DNA methylation in children aged 7-10 years who are engaged in swimming. The aim of the study: to study the characteristics of changes in immunological parameters and epigenetic DNA methylation in children aged 7-10 years involved in swimming. Material and methods. The study involved 30 children aged 7-10 years, who were divided into 3 groups. Group 1 included 10 children aged 7-10 years who were not involved in any kind of sport - control. Group 2 included 10 children aged 7-10 years who had been swimming for 1 year. Group 3 included 10 children aged 7-10 years who had been swimming for 3 years. Cytokines, DNA methyl-transferase 1 and 5-methyl-2'-deoxycytidine content were determined by ELISA using standard kits. Statistical data processing was performed using Microsoft Office Excel 2010 by the variation statistics method with calculation of arithmetic means and their errors (M±m). The statistical significance of differences between independent samples with normal distribution was assessed using Student's t-test. Differences were considered significant at p<0.05. Research results. In children of 7-10 years old engaged in swimming, with an increase in the duration of the usual training process, compared with children who are not engaged in any kind of sports, there was a significant increase in blood after 1 year, and after 3 years of training, a significant decrease in the indicators taken into account, more pronounced in the study of IL-6, TGF-β1 and less pronounced in the study of TNF-α, IL-10. During the peak of training load, similar, but more pronounced changes in these indicators were detected compared to the indicators of the usual training process. When studying the activity of DNA methyl transferase 1 and the content of 5-methyl-2'-deoxycytidine with an increase in the duration of swimming, an unreliable decrease in these indicators was observed after 1 year and a significant decrease after 3 years of training compared with children who do not engage in any sports. During the peak training load, there was also a significant decrease in these indicators after 1 year and more pronounced after 3 years of training, relative to the results of children who do not engage in any kind of sports. Conclusion. With an increase in physical activity in duration and intensity, the level of cytokines, the activity of DNA methyltransferase 1 and the content of 5-methyl-2'-deoxycytidine decrease, which indicates a decrease in adaptation processes.